An analysis of Sustainable Development Goals in Italian cities: Performance measurements and policy implications. (September 2022) - D'Adamo, Idiano; Gastaldi, Massimo; Ioppolo, Giuseppe; Morone, Piergiuseppe
Abstract: The Sustainable Development Goals (SDGs) aim to achieve a more inclusive, resilient, safe and sustainable society. Policy makers, together with entrepreneurs and citizens, are called to a great challenge to optimize land use. This work, through a multi-criteria decision analysis (MCDA), aims at comparing the sustainability of 103 Italian cities through the evaluation of 45 SDGs' indicators, ranking cities on the base of their performance. Results show strong disparities across Italy with three northern cities at the top of the ranking and many southern cities at the bottom. The analysis then creates a framework based on experts' view composed of 21 criteria that would facilitate the development of a sustainability plan. A hybrid methodology based on the Analytic Hierarchy Process (AHP) and the 10-point scale is used to rank among the criteria. Selected experts underlined how sustainable policy and green investment are enabling factors of sustainable cities, but political stability and streamlined public spending are also essential to achieve this goal. The analysis offers insights for different categories of stakeholders and invites to measure and monitor the progress of cities towards SDGs proposing eight directions (policy, economy, operations, environment, organization, staff, society and human). Graphical Abstract: ga1 Highlights: A multicriteria analysis to assess the sustainability of the Italian cities. A new hybrid approach based on 10-point scale and AHP is proposed. Results show strong disparities across Italy between north and south. Sustainable policy and green investment enabling factors of sustainable cities. Eight directions are proposed for making Italian cities more sustainable.